Shaping Emotional Labor Practices in the Sharing Economy - Bucher, Eliane; Fieseler, Christian; Lutz, Christoph; Newlands, Gemma (Theorizing the Sharing Economy, 2020)
Abstract Independent actors operating through peer-to-peer sharing economy platforms co-create service experiences, such as shared car-rides or home-stays. Emotional labor among both parties, manifested in the mutual enactment of socially desirable behavior, is essential in ensuring that these experiences are successful. However, little is known about emotional labor practices and about how sharing economy platforms enforce emotional labor practices among independent actors, such as guests, hosts, drivers, or passengers. To address this research gap, we follow a mixed methods approach. We combine survey research among Airbnb and Uber users with content analysis of seven leading sharing economy platforms. The findings show that (1) users perform emotional labor despite not seeing is as necessarily desirable and (2) platforms actively encourage the performance of emotional labor practices even in the absence of direct formal control. Emotional labor practices are encouraged through (hard) design features such as mutual ratings, reward systems, and gamification, as well as through more subtle (soft) normative framing of desirable practices via platform and app guidelines, tips, community sites, or blogs. Taken together, these findings expand our understanding of the limitations of peer-to-peer sharing platforms, where control over the service experience and quality can only be enforced indirectly.